KEMATANGAN KARIR KARYAWAN YANG SEDANG MENGHADAPI QUARTERLIFE CRISIS DI PERUSAHAAN X JAKARTA SELATAN - Chandra Yudistira Purnama; Kelly Febriza Dwita Juwana; Afini Freudwi Asri (Institut Pendidikan Tapanuli Selatan, 2023)
The purpose of this study is to determine the description of the career maturity of Company X employees who are facing a quarterlife crisis. The theory used in this study is Super's career maturity (1953). This research is a quantitative study with descriptive research type and uses Snowball Sampling technique with a population of 41 employees. The measuring instrument used in this study is a questionnaire made by researchers based on the dimensions of Super's theory. The reliability of the measuring instrument made has a coefficient of 0.76. Based on data processing, the results show that 90.2% of employees of Company X South Jakarta fall into the category of career maturity while 9.8% of employees of Company X South Jakarta fall into the category of career immaturity. Employees of Company X South Jakarta who fall into the category of not career mature, should conduct training to improve their abilities and skills or attend various seminars to broaden their horizons related to the career world.